Trajetórias socioespaciais das estudantes da comunidade quilombola de cocalinho a universidade federal do tocantins. - ARAUJO, Fernanda Neves de (Universidade Federal do Tocantins, 2023)
The present work aims to understand the trajectory taken by university students from the Quilombola Community of Cocalinho-Tocantins to the urban center of the city of Araguaína-Tocantins, as well as to identify the adversities encountered in the course of their displacement. The methodology used in the research consists of descriptive research in which we sought to understand and describe the phenomena that guide the students to take this path and analyze the agents that are inserted in this dynamics of coming and going made by them. Data collection was obtained through primary data that are data collected from questionnaires and interviews made by the researcher and secondary data that are already existing data carried out by other researchers. The research proceeds to the empirical investigation identified through the Case Study, in which the research was carried out in the field/in the community, where seven (7) students who are enrolled in evening courses in Biology, Cooperatives, Tourism were interviewed , Physics and History who are aged between 18 and 38 years old, and one (1) resident of the community, the information collected was made through questionnaires via Google Forms, three (3) were in total, and via whatsapp. The spatial focus of the research is on the Quilombola Community of Cocalinho, which is located in the state of Tocantins and is part of the city of Santa Fé do Araguaia, a community that has strong traces of its ancestors and preserves contemporary traditions. The time frame was delimited between the year 2017 to 2021. The research is important for Geography as the reader will understand the plurality and dynamics existing in geographic categories, in particular place and territory, understanding that the categories can be used over a social context in which the interlocutors produce in this space their countless meanings and notions of belonging. Dialogue mainly for the elaboration of this research with the authors Yi-Fu Tuan, Livia de Oliveira, Werther Holzer, Sylvia Cavalcante and Lana Mara Andrade Nóbrega. The results present in the research demonstrate how important and significant it is to study about these women and about their place, which brings resistance and struggle in its symbology.